Up in the garden and down in the dirt - Messner, Kate (Chronicle Books, 2015)
"Up in the garden, the world is full of green--leaves and sprouts, growing vegetables, ripening fruit. But down in the dirt there is a busy world of earthworms digging, snakes hunting, skunks burrowing, and all the other animals that make a garden their home. In this exuberant book, discover the wonder and activity that lie hidden between the stalks, under the shade of leaves ... and down in the dirt."--